Ação de azitromicina, espiramicina e da associação de sulfadiazina e pirimetamina na infecção por cepas atípicas (Udi1-CH05 e Udi2-CH05) de Toxoplasma gondii em células trofoblásticas humanas (linhagem BeWo) - Ribeiro, Mayara (2013)
Toxoplasma gondii is an obligate intracellular parasite that infects various cell types. There are three predominant lineages of T. gondii, however, distinct pattern is seen in South America and Africa, which is populated by different lineages showing more atypical genotypes. The transplacental passage of parasites could impaired fetal development and also could cause abortion. Conventional treatment of toxoplasmosis may cause side effects and resistance of parasites, because of that, development of studies with new drugs are necessary. In this context, the present study aimed to verify the susceptibility of BeWo cells after infection with Udi1-CH05 or Udi2-CH05 T. gondii strains and the effect of azithromycin, spiramycin and association of sulfadiazine and pyrimethamine in cells infected with these strains. BeWo cells were treated with different concentrations of drugs to evaluate cell viability by MTT assay. The concentration from 400 μg/ml of drugs reduced cell viability. Parasites of Udi1-CH05 strain infected more cells than Udi2-CH05. Furthermore, infection and intracellular replication indexes were reduced after azithromycin treatment. Higher susceptibility of BeWo cells after Udi-1-CH05 infection may be related to decrease TNF- α production. Moreover, reduced parasitism of this strain by drugs is not related to the cytokines analyzed, but with mechanisms to keep the strain infection. Reduction of parasitism of Udi2-CH05 by treatment with azithromycin may be related to the decreased production of IL-12. Thus, this study demonstrated that BeWo cells are more susceptible to infection by Udi1-CH05 than Udi2-CH05 and treatment with azithromycin was more effective in controlling infection and replication of parasite than conventional treatments used.